Kinematic and Dynamic Analysis of a Cable-Climbing Robot. (23rd July 2015) - Fengyu, Xu; Jingjin, Shen; GuoPing, Jiang
To inspect broken cables or a cracked protective layer on cable-stayed bridges, a cable-climbing robot has been proposed and designed. In this paper, the complex 3D obstacles that may be encountered on cables are theoretically described, in order to investigate the obstacle-climbing capability of the cable-climbing robot. A climbing model is then proposed and used to design the robot. In the climbing model, two driven wheels are independently supported with a spring. Kinematics and dynamics models are further derived for the obstacle-climbing capabilities of the driving and driven wheels of the robot. In addition, the robot's obstacle-climbing tracks and its obstacle-climbing performance are simulated. Payload and obstacle-climbing experiments were conducted on the climbing robot in the laboratory. Based on the results of the simulation and the experiments, we obtained the variation of the driving torque in obstacle climbing. The contribution of this paper is intended to provide a basis for the precise motion control of the robot.